Epic content marketing : break through the clutter with a different story, get the most out of your content, and build a community in Web3 - Pulizzi, Joe; Piper, Brian (Web content consultant) (McGraw Hill, 2023)
"From the "godfather of content marketing" this completely revised and expanded edition brings marketers fully up to date on the newest content marketing methods and tools, including Web3 When Epic Content Marketing was first published eight years ago, content marketing was just starting to pick up speed in the marketing world. Now, this approach which includes everything from blogging to YouTube videos to social media is the core of most organizations' marketing plans"--